Learning the Secrets of the Craft Through the Real-Time Experience of Experts : Capturing and Transferring Experts’ Tacit Knowledge to Novices - Sophie Le Bellu (Perspectives Interdisciplinaires sur le Travail et la Santé)
Mass retirement in the baby-boomer generation has led to the current challenge of renewing mentoring in skilled trades, which have traditionally made it possible to transmit the know-how required in manual expertise. A study conducted with France’s largest electricity supplier investigated how the combination of Activity Theory, video ethnography, and psychological verbalisation methods can help to enhance both the preservation of knowledge capital and occupational training. The study led to the development of a novel method for capturing and transferring tacit and explicit knowledge embodied in professional gestures of experts through the building of a new kind of educational media for occupational training. This device, called MAP, allowed operators to learn directly through the real-time experience of experts. A qualitative evaluation of the device showed an improvement in training. These results convinced the company to adopt the device for institutional use. This demonstrates the proposed method’s usefulness for tacit knowledge capture and transfer.